2021
DOI: 10.3390/su13094902
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Development of Sustainable Tourism in Pakistan: A Study of the Role of Tour Operators

Abstract: The literature on sustainable tourism is scant, particularly in the least developed countries. Very few studies touch upon the concept and no holistic theoretical or conceptual frameworks around the idea of sustainable tourism have been formulated. This study aims at exploring the role of tour operators in developing sustainable tourism in Pakistan and how the tour operators (TOs) conceive their role in this regard. TOs were reached through phone calls, emails, and virtual sources as face-to-face interviews we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…To achieve this objective, in the first place, we examined the factor loadings of all variable items. It was revealed that no factor loading was below 0.7 which shows that all values were well-above the minimum acceptable range (≥0.5) [ 87 , 88 , 89 , 90 ]. This was important to see whether a sheer amount of variance in a particular variable is explained by a variable item or the error term.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve this objective, in the first place, we examined the factor loadings of all variable items. It was revealed that no factor loading was below 0.7 which shows that all values were well-above the minimum acceptable range (≥0.5) [ 87 , 88 , 89 , 90 ]. This was important to see whether a sheer amount of variance in a particular variable is explained by a variable item or the error term.…”
Section: Resultsmentioning
confidence: 99%
“…We acknowledge the efforts of Hayes, who introduced this macro which is helpful in calculating different complex models. 136 , 137 The predictor and moderator variables were mean-centered before performing SEM to test the conditional effect of RS. Similarly, an interaction term was also generated by taking the product of ICSR and RS.…”
Section: Resultsmentioning
confidence: 99%
“…We employed structural equation modeling (SEM) to test the hypothesized relationships [ 149 , 150 , 151 ]. For this purpose, we considered AMOS software.…”
Section: Resultsmentioning
confidence: 99%